Women's Resistance to the Issue of Dispossession of Living Space: An Ecofeminism Study - Desrianti, Febrina (Talenta Publisher, 2025)
It is very important for us to understand more deeply the relationship between humans and the universe, especially in the current era of capitalism, because reflecting on human actions reveals a significant misunderstanding of the importance of this relationship with the universe. Many people view the universe (the fruits of the earth) merely as a means to fulfill their basic needs. This capitalist system is a precursor to the condition of the universe's disequilibrium, which in practice involves extractive reinforcement and can cause significant damage to the Earth. In addition, the numerous cases of coastal reclamation and land grabbing are characteristic of the results of the current extractive capitalist system. The living space of the community has been taken over for the interests of only a few groups of people. As a result, the subordinated society does not merely remain silent in the face of such occurrences, but also demonstrates their resistance as a way to defend their living space, especially for women who often find themselves in vulnerable situations experiencing injustice in exercising their rights to power. Keyword: Resistance, Capitalism, Women